Determinants of health data needs of community members in Nyando Sub-County, Kisumu, Kenya - Kilonzo, Henry Munyao; Othero, Doreen; Guyah, Benard (International Journal Of Community Medicine And Public Health, 2025)
Background: Health data is key in healthcare. There exist gaps between the available data and data needs of the community members. The objective of this study was to establish the determinants of health data needs of community members in Nyando Sub-County, Kenya. Methods: This was a 12-month interventional cohort study. 330 participants were selected a population of 1,200 using Yamane’s formula. Chi-square test was used to determine association between categorical variables (health data needs of the participants and socio-demographic and economic variables). Cramér’s Phi statistics indicated the strength of associations between categorical variables demonstrating significant associations at chi-square. Results: The study established the existence of a significant association between gender and need for health data on prevention of malaria and health rights [chi-square; (χ2), p=0.0001]. Similarly, marital status was significantly associated with need for health data on health rights (p=0.011), however, the association was weak; Cramér's Phi; Φc of 0.142. The results showed a significant association between gender and need for health data on disease outbreaks in all the assessed socio- demographic and economic features. Similarly, marital status was significantly associated with need for health data on psychosocial support (p=0.001), whereby the association was moderate; Cramér's Phi; Φc of 0.212. Conclusions: In conclusion, the study revealed that the community members have health data needs some of which are unmet. Gender and age are key determinants on the type of health data needed by community members.